Molecular taxonomy provides new insights into Anopheles species of the neotropical arribalzagia series (2015)
ABSTRACT: Phylogenetic analysis of partial mitochondrial cytochrome oxidase c subunit I (COI) and nuclear internal transcribed spacer 2 (ITS2) sequences were used to evaluate initial identification and to investigate phylogenetic relationships of seven Anopheles morphospecies of the Arribalzagia Series from Colombia. Phylogenetic trees recovered highly supported clades for An. punctimaculas.s., An. calderoni, An. malefactor s.l., An. neomaculipalpus, An. apicimacula s.l., An. mattogrossensis and An. peryassui. This study provides the first molecular confirmation of An. malefactorfrom Colombia and discovered conflicting patterns of divergence for the molecular markers among specimens from northeast and northern Colombia suggesting the presence of two previously unrecognized Molecular Operational Taxonomic Units (MOTUs). Furthermore, two highly differentiated An. apicimacula MOTUs previously found in Panama were detected. Overall, the combined molecular dataset facilitated the detection of known and new Colombian evolutionary lineages, and constitutes the baseline for future research on their bionomics, ecology and potential role as malaria vectors.